THE ROLE OF THE STRUCTURAL PROTEINS IN THE NON-VIRAEMIC TRANSMISSION OF TICK-BORNE ENCEPHALITIS VIRUS - M. A. Khasnatinov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
There are 3 subtypes of tick-borne encephalitis virus (TBEV) distinguished, at present time: European (EU), Siberian (SIB) and Far Eastern (FE). The former one is associated with Ixodes ricinus tick, whereas the latter two - with I. persulcatus. The circulation of TBEV in nature is mediated by the non-viraemic transmission, between infected and. uninfected ticks co-feeding on the same hosts and. it was shown that transmission rate of «Hypr» strain (EU subtype) is much higher than rate of «Vasilchenko» strain (SIB subtype) - 60 and 5 % respectively. To reveal the viral determinants of transmission efficacy, we constructed the series of recombinant viruses with gradually exchanged genes coding structural (str) and. non-structural (ns) viral proteins. The recombinant virus Hypr[str]Vs[ns] achieved the rate of non-viraemic transmission of 70 %. The introduction of separate structural genes of Hypr into Vs infectious clone has enhanced the transmission efficacy as well, though not to such extent as entire structural region but up to 33 % only. Thus, it was shown that efficacy of non-viraemic transmission of TBEV depends from properties of viral structural proteins mainly.